Effects of nitroquine on ultrastructures and cytochrome oxidase of exoerythrocytic Plasmodium yoelii in rat liver - Chen Xiao-Hong; Hu You-Mei; Liao Ya-Qing; Ke Jin-Xing; Zhang Wen-Jun (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of nitroquine acetate (NA) on the ultrastructures and cytochrome-c oxidase (CCO) of exoerythrocytic forms (EEF) of Plasmodium yoelii. METHODS: Rats were inoculated with sporozoites directly into the liver. After 48 h rats were killed. Rat liver thin sections were incubated in histochemical reaction medium, then examined by transmission electron microscopy. NA (2 mg.kg-1) was fed to rats 3.5 h and 14 h before killing the rats. RESULTS: At 3.5 h, in the parasites there appeared swelling and proliferation of mitochondria, dilation of endoplasmic reticulum, and reduction of the electron density of parasites' nuclei. The structures of the parasites disintegrated to form many autophagocytes 14 h after exposure to NA. The reaction products of CCO still existed until 14 h after using NA. CONCLUSION: CCO was not the starting point of NA action. NA interferes with the structure and function of the cytoplasm and nucleus of malaria parasites and exerts its antimalarial effects in many aspects.